2001
DOI: 10.1097/00042728-200102000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Leg Vein Telangiectasia with a New 940 nm Diode Laser

Abstract: background. A variety of lasers have been used in an attempt to treat leg vein telangiectasia objective. To evaluate the feasibility of a new 940 nm diode laser for the treatment of leg vein telangiectasia. methods. Thirty-one patients with leg vein telangiectasia were treated with a diode laser; 26 of these with 940 nm, 300-350 J/cm 2 , 40-70 msec, 1.0 mm handpiece, one pass, and 5 of these with 940 nm, 815 J/cm 2 , 50 msec, 0.5 mm handpiece, one pass. Each subject had three treatments of the same site at 4-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The design of the study, the patients' characteristics, and the laser parameters used have been described previously. 5 In brief, 20 female patients were available for the present longterm follow-up study. They all had leg vein telangiectases on various locations on their calves and shins with a vessel diameter of less than 1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the study, the patients' characteristics, and the laser parameters used have been described previously. 5 In brief, 20 female patients were available for the present longterm follow-up study. They all had leg vein telangiectases on various locations on their calves and shins with a vessel diameter of less than 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 A new 940 nm diode laser designed according to this rationale has been reported as effective and safe for the treatment of leg vein telangiectasia. 5 These reports are based on shortterm clinical assessments performed 4 weeks after the last of three treatment sessions. Clinical experience with sclerotherapy of leg vein telangiectasia suggests that longer follow-up periods are needed to fully assess the definite clinical end results in terms of vessel clearance.…”
mentioning
confidence: 99%
“…Although lasers and light sources in the near infrared waveband can penetrate deeper into tissue, concomitant with longer wavelengths, the pigment in hemoglobin becomes less of a powerful photoacceptor, being replaced by proteinaceous and other molecular targets and, after around 900 nm, water. Diode-based laser systems have lately been reported in the treatment of leg veins because of their ease of generating true continuous pulses of longer duration compared with flashlamppumped systems such as the Nd:YAG and pulsed dye lasers in which the ''long pulsed'' versions consist of a train of micropulses due to the difficulty in obtaining a continuous long pulse from flashlamp pumping, thus offering greater efficacy with less in the way of side effects [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…• Another study demonstrated over 75 % clearance after 4 weeks of treatment in 12 out of 26 patients using a 940 nm diode laser [ 35 ].…”
Section: Long-pulse Infrared Alexandrite Lasermentioning
confidence: 98%